The Mularz Paradox—Relativistic Discrepancies in The Resistivity of Cylindrical Electrical Conductors Travelling at Near Light-Speed—A Thought Experiment - Mularz, Stephen (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Most of us are familiar with Einstein’s now-famous relativistic thought experiments—his stationary-versus-moving ‘light clock’ and the interstellar twin astronauts aging at different rates especially stand out.[1] In this simple thought experiment the author wishes to propose a heretofore unrecognized set of relativity paradoxes involving the predicted electrical resistivity of long cylindrical conductors when moving at or near light-speed.